Wordsworth and Beethoven : the poetics of music in the romantic era - Lee, Claudia Zhi Xuan (2018)
The spiritual poet and teacher Hazrat Inayat Khan taught us that 'One moment standing in the midst of nature with open heart is a whole lifetime, if one is in tune with nature' (14). Since the beginning of time, the natural landscape has appealed to us human beings because of nature's universal therapeutic ability that attracts us to it, compelling us to create art in the form poetry and music. Two prominent figures of the Romantic era will be studied in this proposal, poet William Wordsworth and musician-composer Ludwig Van Beethoven. Both men were lonely; either by temperament (how can we forget Wordsworth's most famous poem, 'I wandered lonely as a cloud'?), or 'driven to loneliness by circumstances and sought comfort in the forms of outward nature, predisposing them to inwardness and a continual preoccupation with the self'(Gross, 143). Shaped by the same historical forces and revolutionary consciousness of self and nature, Wordsworth and Beethoven grappled with self-estrangement and achieved a degree of victory over their adversaries, immortalized through their works. For both, the sound of poetry and the sound of music reflect the natural environment and embody the power to present itself to human consciousness. What, then, is the common thread tying these two Romantic forms together? What then, is the 'single celestial rhythm' that flows through musical and poetic works? To delve deeper into this subject, Beethoven's Opus 8, No. 13, 'Pathetique' will be studied in relation to Wordsworth's The Prelude. Both works exist simultaneously as dialogue to each other, as intentional and communicative discourse, providing deeper insight when read in comparison. This study explores will be conducted with a focus on the role of nature in creating self consciousness that manifests itself in music and poetry, and how reading these two forms in conversation provide new insights to understanding ourselves and our environment.